Comparative experimental and modelling study of the thermal and thermo-mechanical properties of LLDPE/wax blends - Mafereka F. T. Mosoabisane (14151309) (2022)
The interactions and morphology of molecules in a polymer blend influence the physical properties of the blend. However, little is known about the influence of molecular interaction and morphology on the thermal and mechanical properties of LLDPE/wax blends. Although cooling rate can be used to investigate blends' thermal and mechanical properties, it is inadequate to determine interactions between the molecules in the LLDPE/wax blends. However, since the morphology is related to the thermal and mechanical properties of polymer blends and could be related to the cooling rate, LLDPE/wax samples prepared by melt mixing were cooled at different rates. The thermal and mechanical properties of the LLDPE/wax blends were modelled through molecular dynamic simulations. The modelled transitions were compared to experimentally determined mechanical relaxations of LLDPE/wax blends to investigate the effect of wax addition on the blend crystallinity. The crystallization behaviour of the blends was studied by differential scanning calorimetry, dynamic mechanical behaviour by dynamic mechanical analysis, and differences in crystallinity by X-ray diffraction. There were no significant differences between the results for the slow- and quench-cooled samples, confirming the rapid crystallization of both the LLDPE and the wax. Experiments and molecular dynamics simulations confirmed the cocrystallization of wax with LLDPE. Other Information Published in: Journal of Polymer Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10965-022-03136-w